Relationship Between Lipoprotein (a) [Lp(a)] and Cognition in Different Ischemic Stroke Subtypes - Li, Jingjing; Li, Shiyu; Pan, Yuesong; Wang, Mengxing; Meng, Xia; Wang, Yilong; Zhao, Xingquan; Wang, Yongjun (Frontiers in Neurology, 2021)
Background and Purpose: Although elevated serum lipoprotein (a) [Lp(a)] is considered to be a risk factor of ischemic stroke, the relationship between Lp(a) and cognitive impairment after stroke remains unclear. This study investigated the association between serum Lp(a) and cognitive function after acute ischemic stroke (AIS) or transient ischemic attack (TIA). Methods: The study included 1,017 patients diagnosed with AIS or TIA from the cognition subgroup of the Third China National Stroke Registry (CNSR3). Montreal Cognitive Assessment (MoCA) at 2 weeks or discharge, 3 months, and 1 year was evaluated. The primary outcome was cognitive impairment at 1 year, defined as MoCA ≤ 22. The secondary outcome was cognition improvement at 1 year compared with 2 weeks. The association between Lp(a) levels and cognitive function was analyzed. Results: Among the 1,017 patients included, 326 (32.1%) had cognitive impairment at 1 year. Patients with MoCA ≤ 22 at 1 year were older, received less education, and had higher baseline NIHSS, higher proportion of ischemic stroke history, large artery atherosclerosis (LAA) subtype, and multiple infarctions (P < 0.05 for all). Patients with highest Lp(a) quartile had slightly higher percentage of cognitive impairment at 1 year but without statistical difference. In subgroup analysis of LAA subtype, the patients with highest Lp(a) quartile had higher percentage of cognitive impairment at 1 year (adjusted OR:2.63; 95% CI: 1.05–6.61, P < 0.05). What is more, the patients with highest Lp(a) quartile in LAA subtype had lower percentage of cognition improvement at 1 year. However, similar results were not found in small artery occlusion (SAO) subtype. Conclusion: Higher Lp(a) level was associated with cognitive impairment and less improvement of cognition in patients after AIS or TIA with large-artery atherosclerosis subtype.